Down‐regulation of aquaporin 5‐mediated epithelial‐mesenchymal transition and anti‐metastatic effect by natural product Cairicoside E in colorectal cancer - Chen, Chen; Ma, Ting; Zhang, Chao; Zhang, Hao; Bai, Lijuan; Kong, Lingyi; Luo, Jianguang (Molecular carcinogenesis, 2017)
Epithelial‐mesenchymal transition (EMT) has emerged as an important determinant role in colorectal cancer (CRC) metastasis. It has been reported that aquaporin 5 (AQP5) is closely linked to CRC metastasis. However, the effect of AQP5 on the EMT process of CRC remains unknown. The current study showed that overexpression of AQP5 activated EMT in CRC cells. Cairicoside E (CE), a natural resin glycoside compound isolated from Ipomoea cairica, showed promising cytotoxic activity in our previous report. Further investigation found that CE inhibited the expression of AQP5 and the EMT process. Moreover, the inhibitory effect of CE on EMT was reversed by overexpression of AQP5. Importantly, CE also suppressed the EMT and p‐Smad2/3 induced by TGF‐β1. On the other hand, overexpression of AQP5 up‐regulated the p‐Smad2/3, which resulted in the activation of EMT. After silencing of AQP5, CE had no significant effect on EMT markers and p‐Smad2/3 induced by TGF‐β1, indicating that CE inhibited the EMT through down‐regulation of AQP5 and suppression of p‐Smad2/3. CE also inhibited the AQP5 expression in the lung metastatic nodules of HCT‐116 cells in vivo. Our findings suggested that CE may serve as a promising drug for the treatment of CRC metastasis.